2012
DOI: 10.2298/mpns1206244l
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gestational trophoblastic disease: A 10-year experience

Abstract: A retrospective descriptive study about the presence of metastases, epidemiological characteristics and treatment of 104 patients suffering from gestational trophoblastic disease was performed in the period from 1st Jan, 2000 to 31st December, 2010. Of eleven patients who were found to have metastases (10.6%), 72.7% had pulmonary metastases, 27.3 had vaginal, and one patient had both pulmonary and brain metastases. The average age was 33.9. Antecedent molar pregnancy was recorded in 63.6% patients. Invasive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…[18] Our results were in accordance to Rolon et al .,[18] as incidence of CCA and HM were 5 (4.2%) and 115 (95.8%), respectively during 10 years from the 120 registered records. Lazović et al .,[19] in a retrospective descriptive study about the presence of metastases, epidemiological characteristics, and 104 patients with GTD found that IM was more frequent than CCA (63.6%).…”
Section: Discussionmentioning
confidence: 99%
“…[18] Our results were in accordance to Rolon et al .,[18] as incidence of CCA and HM were 5 (4.2%) and 115 (95.8%), respectively during 10 years from the 120 registered records. Lazović et al .,[19] in a retrospective descriptive study about the presence of metastases, epidemiological characteristics, and 104 patients with GTD found that IM was more frequent than CCA (63.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Radiography Chest. The lungs are the most common site of metastasis in GTN [7,36,60]. Chest radiographs are the primary imaging method recommended by FIGO to detect and count lung metastases for purposes of risk assessment in patients with GTN.…”
Section: Us Pelvis Transabdominalmentioning
confidence: 99%
“…CT Chest. The lungs are the most common site of metastasis in GTN [7,36,60]. Approximately 30% to 40% of patients assumed to have nonmetastatic disease by radiographs may have CT evidence of micrometastases [20,[38][39][40].…”
Section: Us Pelvis Transabdominalmentioning
confidence: 99%